Apontamentos sobre o livro “Historia de una montaña”, de Élisée Reclus - Ricardo Jose Nogueira; Olivia Pires Coelho (Confins)
This article is about the book “History of a Mountain”, written by Élisée Reclus (1830-1905), geographer and French anarchist militant. It is aimed to exhibit to the Brazilian Geography public and anarchist activists another piece of work of this remarkable geographer, whose work has been despised.Situations related to the book’s production are also included in the article, based on the letters exchanged between Élisée and his publisher during his time in prison. Then, is it commented about the many chapters in the book which indicates the author’s ability to articulate the scientific discourse with reveries of a nature-loving geographer.